SPRITUALITAS DALAM PENDIDIKAN ISLAM - Mulyadi Hermanto Nasution (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Spiritual-based education must be able to touch the innermost side of the learner or heart, so that learners know and realize that he was created by God, born into the world with the duty of worship, able to live grateful, loving fellow human beings and other creatures because Allah alone, diligent worship, caring for others, respect for parents and teachers. If spiritual values are embedded in the subconscious of the learners, their lives will always be colored with positive, proactive, productive, progressive, participative, and last but not least, humble attitude, tawadhu and taqwa attitudes.When we talk about Islamic education, we must look at both the formal and the non-formal with the understanding and have the principle of integration, balance, equality, lifelong education and the principle of priority to anticipate the misbehavior that can hinder the goal.